Senegal : Second Review Under the Policy Support Instrument, Request for a Twelve-Month Arrangement Under the Exogenous Shocks Facility, and Request for Waivers and Modification of Assessment Criteria -Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2009)
Senegal's second review under the Policy Support Instrument and request for a Twelve-Month Arrangement under the Exogenous Shocks Facility, and request for Waivers and Modification of Assessment Criteria are assessed. Rising food and energy prices have presented a shock to the balance of payments of 5u percent of GDP in 2008. These difficulties have been compounded by significant policy slippages in the form of government payment delays to the private sector and accumulated over 2006-08, which are impacting the real economy.